Does efficiency promote competitiveness of the insurance industry? - Lee, Hui Shan; Cheng, Fan Fah; Md Nassir, Annuar; Ab Razak, Nazrul Hisyam (VGTU Press, 2018)
This paper contributes to the existing literature by examining the efficiency and competitiveness of the Takaful insurance. We employ the Data Envelopment Analysis (DEA) to compute the efficiency of Takaful operators, while Panzar-Rosse (P-R) H-statistic method is used to evaluate the degree of competition. The findings indicate that the inefficiency in Takaful’s operations is affected by the scale of operations but not by inefficiency in managerial practice. Actuaries need to pay attention to estimating provisions for outstanding claims, as this factor is negatively influencing the efficiency of Takaful insurance. Additionally, the managers are cautioned not to overspend on commissions paid to the agents because this will reduce the profit of the Takaful operators. The findings to a very large extent indicate that improvement in efficiency will increase the entry of a more viable competitor to participate in the Takaful industry. The regulators need to implement prudent monitoring of the operations of Takaful insurers because improvements in efficiency will make Takaful operators more competitive. The implications further shed light on the motivation for insurance firms to improve efficiency that enable them to charge lower price to enhance competition which may benefit both the firms and customers.